Association between Community Perception and Willingness to Vaccinated Againts COVID-19 in Surakarta, Central Java, Indonesia - Dewi, Annita Viesta Nirmala; Kharisma, Alya Ayu; Inas, Nailah Salma; Habiba, Chusna; Indriyani, Okti; Dharmawan, Caroline; Jihadillah, Syarifah; Mujahidah, Hibah; Trisiadewi, Kharisma; Ramadhani, Nabila; Wahidah, Nurul Jannatul; Novika, Revi Gama Hatta (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Covid-19 has been declared a pandemic since March 2020 until now, so the government requires the provision of a covid-19 vaccine for all people. The government's vaccination campaign has received various responses from the public, some people accept and some reject the Covid-19 vaccine. This study aims to determine the relationship between public perception of the acceptance of the COVID-19 vaccine in Surakarta.Subjects and Methods: The cross sectional study was conducted in Surakarta. A sample of 65 people aged >12 years was selected by random sampling. The dependent variable was the willingness to receive the covid-19 vaccine. Tthe independent variable was perception. Data was collected by online questionnaire (google form). Data were analyzed by chi square test.Results: There is a relationship between public perception of vaccination and acceptance of the covid-19 vaccine (OR=5.45 ; 95% CI= 2.57 to 11.53 ; p<0.001)Conclusion: There is a significant relationship between perceptions related to vaccines and people's willingness to receive the COVID-19 vaccine.Keywords: covid-19, acceptance, knowledge, rejection, vaccinationCorrespondence: Annita Viesta Nirmala Dewi. Midwifery Study Program, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir Sutami 36 Surakarta, Central Java. Email: contact.anitaviee@gmail.com. Mobile: +6285103027268.Indonesian Journal of Medicine (2021), 06(04): 430-438https://doi.org/10.26911/theijmed.2021.06.04.09